Modal Sosial Inklusif dalam Jaringan Komunikasi Bencana - Damayanti Wardyaningrum (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2016)
This research aims at identifying inclusive social capital on communication network in the disaster preparedness of Merapi explosion in 2010 by operating concepts of communication network, social capital and disaster mitigation. The objects are local people in one of villages in Merapi mountain in Central Jawa. This research used positivistical paradigm using quantitative data and supported by qualitative data. The result shows that there are four inclusive social capitals in the communication network of Merapi: (1) relation with volunteer (2) relations with SAR team and NGO; (3) relation with local government and (4) and traditional relation with Yogyakarta Kingdom. In addition, the interpretaion of inclusive social capital is the existence of reciprocal feedback form local people. Inclusive social capital has facilitated information flow on disaster preparedness, influencing agent that has role as decision maker and supporting individual credibility to get access of resources and as identity builder and Inclusive social capital is recognition of local people. This research has not found yet Inclusive social capital in term of relation between local people and university institution who has many resources to build disaster preparedness.